Utilising Reclaimed Water for Papaya (Carica papaya L.) Cultivation in Cape Verde: A Detailed Case Study - Vanessa Mendoza-Grimón; Regla Amorós; Juan Ramón Fernández-Vera; Ernestina Lopes da Veiga; Maria del Pino Palacios-Díaz (Agronomy)
Papaya (Carica papaya L.) is essential for food security, providing economic benefits in tropical and subtropical regions. However, its high water requirements pose challenges, especially in water-scarce areas like Cape Verde. This study hypothesises that reclaimed water (RW) irrigation can promote papaya production and investigates how water can be managed to ensure sustainability and increase agricultural productivity. An experiment was conducted using Carica papaya L. var Solo-nº8, focusing on subsurface drip irrigation (SDI) with RW. Three irrigation treatments were compared, namely, T1: RW with SDI; T2: RW with drip irrigation (DI); and T3: conventional water (CW) with SDI. The study evaluated crop yields and water use efficiency (WUE) over 13 months, monitoring soil and water quality and papaya growth and yields. Despite quality concerns, RW maintained soil fertility and ensured sustainable reuse. Papaya demonstrated high adaptability and productivity under experimental conditions. T1 significantly increased the cumulative fruit yield (69 t/ha) compared to T2 (65 t/ha) and T3 (62.7 t/ha). T1 also had the highest WUE (5.97 kg/m3), demonstrating the effectiveness of RW and SDI in optimising water use. The results indicate that RW can be a viable alternative to conventional water sources, providing new insights into sustainable agricultural practices and improving food security in arid and semi-arid regions.